Pre-packed alkali activated cement-free mortars for repair of existing masonry buildings and concrete structures. (10th June 2018) - Coppola, L.; Coffetti, D.; Crotti, E.
Highlights: Sustainable alkali-activated slag-based mortars were studied. The influence of powder activator-dosage was investigated. Rheological, physical and mechanical properties are affected by activator dosage. Compressive strength is "tailored" by changing the activator/precursor ratio. Abstract: This paper is aimed to study a ground granulated blast furnace slag activated with alkali powder to manufacture Portland-free mortars for conservation, restoration and retrofitting of existing masonry buildings and concrete structures. Activator/precursor represents the key parameter – not only for elasto-mechanical performances – influencing the rheological properties and the shrinkage: the higher the activator dosage, the higher the consistency class and shrinkage. Moreover, elastic modulus of slag-based mortars is lower than that of OPC-mortars at the same strength class. AAMs seem to be more promising for a sustainable future in construction since the GER and GWP are reduced by about 80% compared with traditional Portland cement mortars with the same compressive strength.